O princípio da proteção especial da família: uma vertente da extrafiscalidade no Direito Tributário - Melo, Samuel de Castro Barbosa (2015)
Resulting from the study of the structural combination of the legal, political and family systems carried out by the Constitution and based on systems theory by Niklas Luhmann, this investigation examines the applicability of the special protection of the family within the national tax system. In general terms, after identifying the structures of the different systems that coexist in the constitutional sphere, this study analyzes the de-patrimonialization and repersonalization of Family Law before constitutional principles. Going deep into the national tax system, we examined the normative dimensions of the limiting principles of the taxing power. Departing from the study of the doctrine and decisions of international Constitutional Courts, it was sought a new conceptual analysis of the principles of tax equality and ability to pay upon the incidence of the principle established in Article 226, caput, of the 1988 Federal Constitution. Other issues like the doctrinal discussion on the evolution and establishment of fundamental rights in international instruments and in the current Constitution, and the transposition of the overprinciple of human dignity under the tax law will also be addressed. It will be also to brought to light the influence of fundamental human rights under the tax law as well as their application to non-taxation of the existential minimum. This study will then examine the various aspects of the normative content of family s special protection principle: institutional guarantee, constitutional limitation on the power to tax, immunizing norm of the family existential minimum and extra fiscal function. The system of family taxation will be addressed, going further to the examination of the techniques adopted in alien and national law. It will be also analyzed the flaws made by national legislation on the taxation of goods and expenses, essential for family maintenance. Finally, the tax on household income will be considered as a tool to promote it, evidencing its extra fiscal aspect